2019
DOI: 10.1155/2019/1474578
|View full text |Cite
|
Sign up to set email alerts
|

In-Vitro Biofilm Formation and Antimicrobial Resistance of Escherichia coli in Diabetic and Nondiabetic Patients

Abstract: Background. Diabetic patients are more susceptible to urinary tract infection compared to nondiabetic patients, Escherichia coli being the most common uropathogen causing UTI. Unreasonable and incorrect antibiotic prescription for UTI in these patients may induce the development of antibiotic-resistant urinary pathogens resulting in delayed recovery and longer hospitalization. In addition to these, biofilm forming capacity of the pathogen may worsen the problem. The main aim of this cross-sectional study (cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 32 publications
3
10
0
Order By: Relevance
“…Escherichia coli showed a high level of resistance to amoxicillin-clavulanic acid, trimethoprim-sulfamethoxazole and nalidixic acid. This result is consistent with the results of a study conducted in Nepal in 2019 [ 29 ]. In studies on E. coli , which causes UTI in Iran, the highest resistance is related to ampicillin, amoxicillin and tetracycline.…”
Section: Discussionsupporting
confidence: 93%
“…Escherichia coli showed a high level of resistance to amoxicillin-clavulanic acid, trimethoprim-sulfamethoxazole and nalidixic acid. This result is consistent with the results of a study conducted in Nepal in 2019 [ 29 ]. In studies on E. coli , which causes UTI in Iran, the highest resistance is related to ampicillin, amoxicillin and tetracycline.…”
Section: Discussionsupporting
confidence: 93%
“…Similar conclusions were drawn by Golia et al (2012), who studied the correlation between biofilm formation of uropathogenic E. coli and antibiotic resistance pattern and documented that biofilm producing isolates exhabited high degree of resistance towards broad spectrum antibiotics. Raya et al (2019) analysed in vitro biofilm formation and antimicrobial resistance of E. coli in diabetic and non-diabetic patients and found that resistance was higher in biofilm producing E. coli compared to nonbiofilm isolates. Risal et al (2018) reported similar conclusions.…”
Section: Resultsmentioning
confidence: 99%
“…In a similar study to ours, involving n 5 208 UPEC strains, Neupane et al concluded that ESBL-positive strains were more common among biofilm-producers [37]. In a Nepalese study by Raya et al, over a thousand cleancatch urine samples were processed from 182 diabetic and 917 non-diabetic patients, respectively: UTIs were more common among diabetic patients (17.4% vs. 42.9%); in addition, biofilm-production was more commonly seen in association with SXT, 3GCs and CIP resistance, and the MDR phenotype [38]. Whelan et al have also assessed the possible predictive power of colony morphology in relation to biofilm-formation in E. coli; however, in their setting, colony presentation on Cysteine Lactose Electrolyte Deficient (CLED) agar had a very low (4%) predictive power, when n 5 50 strong biofilm-producing strains were assessed [39].…”
Section: Discussion Review Of the Literaturementioning
confidence: 99%